PpGpp mediates the growth phase‐dependent regulation of agn43, a phase variable gene, by stimulating its promoter activity. Issue 4 (10th July 2020) - Cabrer‐Panes, Juan David; Fernández‐Coll, Llorenç; Fernández‐Vázquez, Jorge; Gaviria‐Cantin, Tania Cristina; El Mouali, Youssef; Åberg, Anna; Balsalobre, Carlos
Summary: Antigen 43 (Ag43) is a self‐recognizing outer membrane protein of Escherichia coli expressed during intracellular growth and biofilm formation, suggesting a role in infection. The expression of agn43 is under phase variation control, meaning that there are regulatory mechanisms adjusting the percentage of agn43‐ expressing cells in the population, in addition to mechanisms modulating the transcriptional expression level in each expressing cell. Phenotypic and transcriptional studies indicate that Ag43 expression is induced upon entry into the stationary phase in a ppGpp‐dependent and RpoS‐independent manner. The use of single‐cell approaches and phase variation deficient strains let to conclude that ppGpp stimulates agn43 promoter activity, rather than affecting the percentage of agn43 ‐expressing cells. The data highlight the relevance that promoter activity regulation may have, without any involvement of the phase variation state, in the final Ag43 expression output. The agn43 promoter of the MG1655 strain carries an AT‐rich discriminator between positions −10 and +1, which is highly conserved among the agn43 genes present in the different pathotypes of E. coli . Remarkably, the AT‐rich discriminator is required for the positive transcriptional control mediated by ppGpp.